Active sites in modified copper catalysts for selective liquid phase dehydration of aqueous glycerol to acetol - Mane, Rasika B.; Yamaguchi, Aritomo; Malawadkar, Atul V.; Shirai, Masayuki; Rode, Chandrashekhar V. (RSC Advances, 2013)
We report here the influence of oxides of various metals viz. Ba, Mg, Zr, Zn, Al, and Cr in modified copper catalysts, on the formation of different copper species and acid sites responsible for dehydration of aqueous glycerol to acetol. These catalysts were prepared by a co-precipitation method, among which the catalysts having higher acid strength and predominant Bronsted acidity (Cu-Mg, Cu-Zr and Cu-Al) gave the highest acetol selectivity (76-92%), while the catalysts with lower acidity such as Cu-Zn showed very poor (25%) selectivity to acetol in spite of the highest conversion of 68%. Nevertheless, catalysts exhibiting higher activity and acetol selectivity also showed the presence of metallic Cu confirmed by XRD and XANES-EXAFS characterization. Based on these results, two different catalytic pathways have been proposed highlighting the role of Lewis and Bronsted acidity along with the metal sites in individual steps of glycerol dehydration reaction.

Effect of composition and pretreatment parameters on activity and stability of Cu-Al catalysts for water-gas shift reaction - Mane, Rasika B.; Jeong, Dae-Woon; Malawadkar, Atul V.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (ChemCatChem, 2014)
We investigated various Cu species responsible for highly efficient Cu-Al oxide catalyst for the water-gas shift reaction (WGSR). The formation of various Cu species was achieved by systematically varying the Cu-Al composition in the coprecipitated mixed Cu-Al oxides. The Cu-Al composition of 70:30 (Cu-Al-7) was the best for WGSR using the reformate gas composition. In addition, the Cu-Al-7 catalyst reduced under 100% H-2, was relatively stable with time on stream of 100 h, at higher gas hourly space velocity of 36201 h(-1). The structural investigation of our coprecipitated catalysts with varying Cu-Al compositions revealed the formation of nonzero oxidation state copper and metallic Cu to be essential for the observed WGSR activity. In addition, the highest activity and stability of Cu-Al-7 catalysts reduced under 100% H-2 at lower temperature was attributed to particle-size stabilization and a lower extent of Cu aggregation by Cu2O and boehmite phases, respectively, along with the formation of various Cu species during the activation protocol for 12 h. Complete CO2 selectivity without methanation was observed for all the Cu-Al compositions irrespective of their pretreatment conditions.
Keywords: aluminum; Copper; fuel cells; Hydrogen; reduction

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.